Effect of void fraction and friction factor models on the prediction of pressure drop of R134a during downward condensation in a vertical tube - Dalkilic, A. S.; Kurekci, N. A.; Wongwises, S. (SPRINGER, 2012)
The theoretical flow models of homogeneous and separated flow are applied to in-tube condensation to predict the pressure drop characteristics of R134a. The homogeneous flow model is modified by ten different dynamic viscosity correlations and various alternative correlations of total, frictional and momentum pressure drops to take account of the partial condensation inside the tube. Numerical analyses were performed to determine the average and local homogeneous wall shear stresses and friction factors by means of a CFD program. The equivalent Reynolds number model is modified by six different two-phase friction factors to determine the total condensation pressure drop in the separated flow model. The refrigerant side total pressure drops, frictional pressure drops, friction factors and wall shear stresses are determined within a +/- 30% error band. The importance of using the alternative total, momentum and frictional pressure drop correlations for the homogeneous flow model is also shown.
Keywords: LIQUID ANNULAR-FLOW; 2-PHASE FLOW; HEAT-TRANSFER; AIR-WATER; HORIZONTAL TUBES; MINICHANNELS; TRANSITION; VISCOSITY; HOLDUP; R-410A; Thermodynamics; Mechanics